1990
DOI: 10.1002/cm.970170308
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of microtubule dynamics in Reticulomyxa: Unusually rapid length changes and microtubule sliding

Abstract: Microtubule dynamics has been studied extensively in vitro, but comparatively little information is available on the in vivo behavior of microtubules. Here we report on the assembly, disassembly, and sliding of microtubules in the giant freshwater amoeba, Reticulomyxa. We have found that treating the cell with 0.25% trypsin induces the rapid formation of exceedingly flat areas within the reticulopodial network, allowing for the direct observation of microtubule behavior by DIC optics and computer-enhanced vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Among the 9 ␤-tubulin genes in the Arabidopsis genome (the best-characterized plant) there are: 3 which encode 11 acidic residues in this region; 2 with 12; 2 with 13, and 2 with 14; the one carrot sequence for ␤-tubulin has 12 acidic residues (and 12 out of 14 ␤-tubulin genes from other plant species have 11 or more acidic residues; ENTREZ database, NCBI). Reticulomyxa, a protist that has been observed to have interphase microtubules with shortening velocities similar [Chen and Schliwa, 1990] to what we report here, has one ␤-tubulin with 18 acidic residues in this region (ENTREZ, NCBI). Among vertebrates, the majority of ␤-tubulins have 10 acidic residues, or less, in this region [Ludueña, 1993].…”
Section: Discussionsupporting
confidence: 64%
“…Among the 9 ␤-tubulin genes in the Arabidopsis genome (the best-characterized plant) there are: 3 which encode 11 acidic residues in this region; 2 with 12; 2 with 13, and 2 with 14; the one carrot sequence for ␤-tubulin has 12 acidic residues (and 12 out of 14 ␤-tubulin genes from other plant species have 11 or more acidic residues; ENTREZ database, NCBI). Reticulomyxa, a protist that has been observed to have interphase microtubules with shortening velocities similar [Chen and Schliwa, 1990] to what we report here, has one ␤-tubulin with 18 acidic residues in this region (ENTREZ, NCBI). Among vertebrates, the majority of ␤-tubulins have 10 acidic residues, or less, in this region [Ludueña, 1993].…”
Section: Discussionsupporting
confidence: 64%
“…Sliding of microtubules along one another or lengthening of microtubules by polymerization are the likely possibilities. The facts that the rate of elongation of the FLP is virtually identical to the rate of fast axonal transport but is more than an order of magnitude greater than most reported rates of microtubule polymerization in vivo and in vitro (Chen and Schliwa, 1990;Tanaka and Kirschner, 1991) suggest sliding as the mechanism. However, there was a recent report of lengthening of microtubules in vivo at a rate of 1.6 rmlsec (Chen and Schliwa, 1990), and no transporting FLPs formed in the presence of nocodazole or colcemid, drugs that block polymerization, so we cannot now distinguish between these possibilities.…”
Section: Discussionmentioning
confidence: 91%
“…Modern multimode light microscopy and correlative electron microscopy have confirmed these observations and have demonstrated that reticulopodia contain a complex network of branched and anastomosed microtubule bundles that display strong negative form birefringence Allen and others, 1981). These observations were later extended to other Foraminifera such as Astrammina (Bowser and DeLaca, 1985), Reticulomyxa (Chen and Schliwa, 1990) and both Amphistegina and Amphisorus (Travis and others, 1988). The general rules governing microtubule distribution in reticulopodia have been established for representative species and appear to be conserved throughout the group (Travis and Bowser, 1991;Bowser and Travis, 2000).…”
Section: Reticulopodial Transport: Granules and Cell Surface Domainsmentioning
confidence: 87%